Uyku İlişkili Hipermotor Epilepsi - Elçi Karaduman, Alev; Arhan, Ebru (Canpolat, Temel Pediatrik Epilepsi, 2024)
SHE, uykuda görülen hipermotor nöbetlerle karakterize nadir bir epilepsi türüdür. Öykü ve klinik semiyoloji ile tanı konur. Genelde interiktal bulgu görülmemesi nedeniyle tanı koymak güçtür. Bu neden tanı koymada video EEG bulguları kritik öneme sahiptir. Genellikle ilk tercih edilen ilaç gece uykudan önce, düşük doz karbamazepindir. İlaca dirençli SHE olgularında epilepsi cerrahisi de bir seçenek olarak akılda tutulmalıdır. SUDEP açısından önemli risk oluşturur ancak erken tanı ve uygun tedavi ile prognoz iyidir. Nörolojik ve genetik temelleri üzerine daha fazla araştırmaya ihtiyaç vardır. SHE is a rare type of epilepsy characterized by hypermotor seizures during sleep. Diagnosis relies on history and clinical semiology. Diagnosis can be challenging due to the absence of interictal findings. Therefore, video EEG findings play a critical role in diagnosis. Carbamazepine at a low dose before bedtime is typically the first-choice medication. Epilepsy surgery should be considered as an option for drug-resistant SHE cases. SUDEP poses a significant risk, yet with early diagnosis and appropriate treatment, the prognosis is favorable. Further research is needed on its neurological and genetic foundations.